How does PBL Brainwriting Method Supplemented with Concept Mapping Effective to Improve Critical Thinking and Problem-Solving Ability? - Suyitno Aloysius; Rizki Khairani (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to; 1) Determine the effectiveness of PBL brainwriting method supplemented with the concept on improving students' critical thinking skills; 2) Determine the effectiveness of PBL with brainwriting method supplemented with concept mapping on improving students' problem solving; 3) Determine the effectiveness of PBL brainwriting method supplemented with concept mapping on improving students' critical thinking and problem solving skill simultaneously; and 4) To determine the relationship between critical thinking and problem solving. This type of research is a quasi-experiment, sampling using a cluster sampling technique. The instruments of this study used test questions on critical thinking ability and problem-solving ability. The results of the study with the MANOVA test showed that there was a significant simultaneous effects PBL model of the brainwriting method supplemented with concept mapping on critical thinking and problem solving skills, the PBL model of the brainwriting method supplemented with concept mapping is effective in improving students' problem solving skills, the PBL model of the brainwriting method supplemented with concept mapping is effective in improving students' problem solving skills, and here is a correlation between critical thinking and problem solving skills.